Restorative Justice in Addressing Environmental Crimes: A Viable Alternative or a Legal Threat? - Sumaryanto, A. Djoko (PT. Anagata Sembagi Education, 2025)
The enforcement of criminal law against environmental crimes in Indonesia remains largely dominated by a retributive approach that emphasizes punitive sanctions, often neglecting ecological restoration and substantive justice. This article examines the relevance and implementation of restorative justice as an alternative approach to addressing environmental crimes. Using a normative-juridical method supplemented by semi-structured interviews, the study analyzes the legal foundations, opportunities, challenges, and implications of applying restorative justice within Indonesia's environmental legal framework. Findings indicate that while restorative justice offers potential as a more responsive mechanism to environmental harm and victims' rights, its implementation faces significant obstacles, such as regulatory ambiguity, risks of impunity for corporate offenders, and limited community and victim participation. Therefore, strengthening a more specific legal framework, building law enforcement capacity, and ensuring active public involvement are essential to effectively, transparently, and fairly applying restorative justice in resolving environmental crimes.